TERAPI OKUPASI AKTIVITAS WAKTU LUANG PADA PASIEN ODGJ DI YAYASAN PANTI KESEHATAN JIWA AS SHIFA - Sulaihah, Sitti; Nufila Hamzah, Ida; Devi Pratiwi, Eka; Nisa, Khoirun; Buhori, Moh; Maulana, Ferdi; Puji Rahayu, Atik; Amir, Faisal; Suhron, M. (NHM PRESS, 2024)
Mental disorders are the way of thinking (cognitive), will (volition), emotions (affective), actions (psychomotor). This can cause changes in the quality of life of a person with mental disorders (ODGJ). ODGJ patients can be said to be independent if they are able to carry out daily activities without family assistance and are able to take the initiative and do things on their own. One of the treatments to assist in the recovery of ODGJ patients is occupational therapy. Occupational therapy can be done by making crafts. which is related to a product produced through hand skills. the purpose of this study is to determine the effectiveness of making handicrafts in helping to improve the skills of patients with mental disorders. This study used an experimental design method with a sample of 19 ODGJ patients. This activity consists of 3 stages, namely preparation, implementation, and evaluation. The results of this activity show that making handicrafts can increase the effectiveness and skills of patients with mental disorders ODGJ in work.